Pre‐eclampsia and risk of infantile haemangioma. (29th January 2017) - Auger, N.; Fraser, W.D.; Arbour, L.; Healy‐Profitós, J.; Drolet, B.A.
Summary: Background: Infantile haemangioma is the most common tumour of infancy, but the association with pre‐eclampsia is poorly understood. Objectives: We determined the relationship between variants of pre‐eclampsia and risk of infantile haemangioma. Methods: We carried out a retrospective cohort study of hospital data for all live births between 1989 and 2013 in Quebec, Canada. We identified 14 240 neonates with, and 1 930 564 without haemangioma before discharge, and determined whether early‐ or late‐onset pre‐eclampsia was documented on the maternal chart. We used log‐binomial regression to compute prevalence ratios (PRs) and 95% confidence intervals (CIs) for the association between pre‐eclampsia and infantile haemangioma, adjusted for maternal characteristics. Results: The prevalence of any haemangioma was higher for pre‐eclampsia than for no pre‐eclampsia (81·3 vs. 72·9 per 10 000), with a PR of 1·15 (95% CI 1·06–1·25) after adjustment for maternal characteristics. Pre‐eclampsia with onset before 34 weeks' gestation was associated with cutaneous (PR 2·32, 95% CI 1·68–3·21), noncutaneous (PR 3·66, 95% CI 2·49–5·37) and unspecified haemangioma (PR 2·49, 95% CI 1·77–3·49). However, the association between early‐onset pre‐eclampsia and haemangioma was attenuated once long neonatal length of hospital stays was accounted for. There was no association with late‐onset pre‐eclampsia after 34 weeks, and associations were weaker for other variants including severe pre‐eclampsia and pre‐eclampsia with low birthweight. Conclusions: Early‐onset pre‐eclampsia is associated with increased risk of haemangioma at birth, but detection bias due to longer hospital stays and closer follow‐up may be part of the reason. Abstract : What's already known about this topic? Pre‐eclampsia is a novel risk factor for infantile haemangioma, but detection bias has not been evaluated. No study has investigated the severity of pre‐eclampsia in relation to the risk of haemangioma. What does this study add? The risk of infantile haemangioma was greater for early‐ but not late‐onset pre‐eclampsia. The association may be partly related to detection bias, resulting from greater follow‐up of infants born preterm due to severe pre‐eclampsia. Respond to this article